A propósito do mercado de levantamentos cartográficos urbanos no Portugal oitocentista (Chaves, 1881) - Fernandes, Mário Gonçalves (2020)
In 2011, in text from the exhibition catalog on "The Topographic Plan of the City of Porto", by A. G. Telles Ferreira (1892), where a portrait of contemporary urban cartography was outlined, with special emphasis on the second half of the 19th century and first decades of the twentieth century, it was stated that, in the second half of the nineteenth century, "the impossibility of the State's geodetic services to respond to the growing needs of cartography on the part of the city councils, allowed a small market to begin to be outlined for the elaboration of cartographic surveys "(FERNANDES, 2011, p. 9).In 2019, looking for a reason or object to communicate, at the VIII Luso-Brazilian Symposium on Historical Cartography, a subject that involved the city of Chaves, he found himself in the Municipal Historical Archive of Chaves with a simple document that, although apparently unimportant, sent to that statement, contributing, as a puzzle piece, to the consolidation of a discourse on the history of urban cartography and urban planning in Portugal.This is documentation dated from Lisbon and 1881, composed of a letter, addressed to the Mayor of Chaves and accompanied by a "Plan of the City of Chaves at 1 / 10.000", whose existence proves and symbolizes the existence of a market for urban cartographic survey services, developed in the context of the existence of human resources with technical capacity (with military engineers since the 18th century and Manoel de Azevedo Fortes and with civil engineers from the polytechnic schools of Lisbon and Porto, created in 1837) and of the need recognized by the city councils to undertake urban improvements, either because the reality required it, or because the legislation required and/or suggested it. The explanation of facts and circumstances is intended to contribute to the history of urban cartography in Portugal.